The profile of a professional reader: Ivo Vojnović’s reading practices (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is to reconstruct the reading profile of Ivo Vojnović using the literature overview and the analysis of his personal correspondence, in order to answer the research questions suggested in Robert Darnton’s methodological texts. The paper aims to reconstruct not only what Vojnović was reading, but also when, where, how and why he was reading, starting with the question who he was as a reader. The study sets off from bibliographic data (who) on Vojnović, and proceeds to look at the content of his correspondence in three time periods: 1878-1906, 1907-1918, 1919-1929 (when). His place of residence is also stated for each period. The study singled out all references to reading related to both the author and the title (what) and particular segments (how and why). Research results give an insight into Ivo Vojnović’s reading world, providing not only the list of authors and titles of books he read, but also his attitude towards what he read, and the context and reasons behind his reading interest. This partly reconstructs the reading profile of Ivo Vojnović as an expert in Croatian and European classical and contemporary literature, a passionate reader bridging European and Croatian culture and literature, in which he for the first time introduced the elements of modernity and symbolism. A study of other available sources that contain the information on Vojnović’s reading (diary entries, literary, theoretical and historical studies of his work, etc.) would give a more holistic insight into possible interpretations of his reading profile.
Keywords: Ivo Vojnović; reading; reading practices; personal correspondence as a historical source; reading profile; history of reading